The efficacy of cognitive behavioral therapy for suicidal ideation in depression:a systematic review and network meta-analysis of randomized clinical trials - Huang, Wenyan; Pan, Qun; Ma, Hui; Na, Lina; Yang, Hao; Wu, Mengjiao (Frontiers in Psychiatry, 2025)
BackgroundSuicidal ideation exhibits a strong correlation with mortality rates among individuals diagnosed with depression. Cognitive behavioral therapy (CBT) may exert an influence on suicide-related outcomes in patients with depression. We examined the impact of CBT on suicidal ideation and depressive symptoms in depression.MethodsBy searching PubMed, Cochrane Library, EmBase, Web of Science, and PsycINFO databases (from inception to December 31, 2024), we identified randomized controlled trials (RCTs) of CBT for patients with depression. Suicidality was assessed explicitly as an endpoint utilizing clinically established psychometric scales with validated properties. The trials compared CBT for depression against control conditions in adults with depression, and reported findings pertaining to suicidal ideation. Independent pairs of reviewers were responsible for selecting studies and extracting relevant data. We evaluated the effects of CBT on suicide outcomes through random-effects model pairwise and network meta-analyses utilizing Stata 18.0. Risk of bias was assessed with the Cochrane risk-of-bias tool (version 2).ResultsIn this systematic review and network meta-analysis, 12 randomized clinical trials were selected from 14 articles (as 3 articles came from the same study and were therefore analyzed together), involving 1336 participants. In terms of suicidal ideation, after the intervention, CBT demonstrated comparable immediate efficacy in diminishing suicidal thoughts when compared to conventional treatment and the control condition. During follow-up, CBT was more effective than the control group (SMD=-6.98, 95%CI (5.71,8.24)). In terms of depressive symptoms, after the intervention, CBT had certain advantages compared with the control group (SMD = 3.11, P<0.05). During follow-up, CBT was more effective than the control group (SMD = 4.54, 95%CI (2.14, 6.95)).ConclusionCBT may reduce suicidal ideation and depressive symptoms among patients with depression. However, more randomized controlled trials (RCTs) are needed to elucidate this effect. In psychological intervention trials for depression, monitoring and reporting of suicide-related adverse events should be enhanced.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024626377, identifier (PROPSERO).